Tribute to the unsung heroes of small-scale food production - International Livestock Research Institute (International Livestock Research Institute, 2011)
A hitherto disregarded vast group of farmers – those who farm both crops and livestock – hold the key to feeding the world in coming years. Most of the world's 'mixed' farmers are smallholders tending rice paddies or cultivating maize and beans while raising a few animals. An ILRI-led research report indicates that this group is likely to play the biggest role in global food security over the next several decades (see ILRI Corporate Report 2009-2010, 'Back to the Future: Revisiting mixed crop-livestock systems'). This photofilm celebrates these 'unsung heroes' – both the mixed farmers themselves and their farm animals.